Urban environment assessment: special reference to terrestrial and aerial photographic approaches - Hadi Sabari Yunus (Indonesian Journal of Geography, 1986)
The following discussion particularly stresses the techniques or research methodologies concerned with urban environment assessment. Given the fact that monitoring the quality of the urban environment is prime, some practical approaches to that problem are seriously needed. Due to the complex nature of the urban environment in terms of the elements, interrelationships of elements, and dynamic nature of their interactions, the author devises a model in the form of a combination approach to assess the urban environmental condition.The variety of urban environments reflects the social, economic, cultural, political, technological and demographic background of the nation and accordingly there should be a wise selection of the applied techniques and the environmental criteria used for assessing the urban environmental condition.The combination approach is an integration of terrestrial and aerial photographic approaches. Since each of the aforementioned approaches has its own weaknesses, the combination approach is expected to cover those weaknesses and can give more effective, accurate and reliable data on the urban environmental assessments.